2021
DOI: 10.1111/jep.13641
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and aftermath of the COVID‐19 lockdown among community‐dwelling older people in Serbia: A qualitative study

Abstract: Rationale and Aim: At the beginning of the COVID-19 pandemic in March 2020, the Serbian government instituted a 24-h curfew for people aged ≥65 years for 2 months. The aim of this study was to examine the experiences and perceptions of curfew for older people in Serbia 15 months after the curfew had ended.Methods: In-depth interviews were carried out with 23 older adults from urban areas in Serbia. We identified the first three participants, while others were selected using the snowballing method. The intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Sheer arrogance on their part and no sanctions applied" (p.11). Although one study reported benevolent ageism (Derrer-Merk et al,2022c) most studies found hostile ageism (Banerjee & Rao, 2021;Derrer-Merk et al, 2022c;Falvo et al, 2021;Gazibara et al, 2022;Hafford-Letchfield et al, 2022;Prigent et al, 2022). One study reported racism and its negative impact on existing friendships "I can tell some people are blatantly despising us.…”
Section: Theme 2 Discriminationmentioning
confidence: 99%
See 4 more Smart Citations
“…Sheer arrogance on their part and no sanctions applied" (p.11). Although one study reported benevolent ageism (Derrer-Merk et al,2022c) most studies found hostile ageism (Banerjee & Rao, 2021;Derrer-Merk et al, 2022c;Falvo et al, 2021;Gazibara et al, 2022;Hafford-Letchfield et al, 2022;Prigent et al, 2022). One study reported racism and its negative impact on existing friendships "I can tell some people are blatantly despising us.…”
Section: Theme 2 Discriminationmentioning
confidence: 99%
“…Seven studies reported on how the mass media impacted participant's well-being (Derrer-Merk et al, 2022c;Falvo et al, 2021;Fiocco et al, 2021;Gazibara et al, 2022;Goins et al, 2021;Mahapatra et al, 2021;Sangrar et al, 2021). Sangrar et al (2021) investigated how older adults responded to COVID-19 messaging: "My reaction was to try to make sure that I listen to everything and [I] made sure I was aware of all the suggestions and the precautions that were being expressed by various agencies…".…”
Section: Theme 1 Risk Communication and Risk Perceptionmentioning
confidence: 99%
See 3 more Smart Citations